FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN SUB SEKTOR PLASTIC AND PACKAGING - Hari Dewi Retnosari; Hendra Hendra (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to examine the factors that influence dividend policy. The independent variables in this study consist of return on equity, leverage, company growth, company size, and managerial ownership structure. The data in this study are plastics and packaging sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2010 to 2020. This study uses 5 companies and 55 samples and the sample selection procedure used is the purposive sampling method. The research test used descriptive statistics dan multiple panel regression analysis. Debt to equity ratio is the only variable has a negative influence on dividend policy, and the rest are not influencing dividend policy. It’s because a company which has a high debt cannot afford dividend to stockholders, they should pay their liabilities first, so the dividend payment will decrease.